(untitled) (Mustansiria Dental Journal, 2018)
The aim of our study was to analyze the stress and anxiety in patients undergoing routine dental extraction, by the assessment of cortisol in saliva, which can be considered as one of the major hormones that is released during stressful events. After obtaining the ethical approval and the patients were consented for their role in this study, we examined 26 patients (13 males, and 13 females).The age ranged from 29-42 with mean age of 36.2. We collected three salivary samples from each patient after asking him to chew on a cotton roll to stimulate salivary secretion. The first sample was obtained 10 minutes prior to local anesthetic injection, the second sample collected 6-8 minutes after the local anesthetic injection, and third sample acquired 10-15 minutes post-extraction. The samples were assessed and analyzed using ELISA immunoassay (competitive inhibition enzyme immunoassay technique). Statistical analysis was performed using SPSS statistical software (version 19).ANOVA and t-test were applied to obtain the significance and correlation between the examined samples. Significant difference was shown among the three samples (P-Value =0.002). The mean value in the third sample (post-extraction salivary sample) was considerably high when compared to the other samples (Mean ± SD = 0.184± 0.184, 0.307 ± 0.121 and 0.357 ± 0.141) respectively, which positively correlates with the patient’s level of stress. Cortisol concentration in μg/dl in percentages between each sample and the percentages, 50%, were0.105 μg/dl, 0.295 μg/dl and 0.410 μg/dl, (75 %) were0.348 μg/dl, 0.410 μg/dl and 0.443 μg/dl and (90%), 0.443 μg/dl, 0.468 μg/dl and 0.518 μg/dl. Our study revealed that salivary cortisol is within its highest levels after extraction in 15 minutes.